If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying mx + 4 = 3x + -1n Reorder the terms: 4 + mx = 3x + -1n Reorder the terms: 4 + mx = -1n + 3x Solving 4 + mx = -1n + 3x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + mx = -1n + -4 + 3x Combine like terms: 4 + -4 = 0 0 + mx = -1n + -4 + 3x mx = -1n + -4 + 3x Reorder the terms: mx = -4 + -1n + 3x Divide each side by 'x'. m = -4x-1 + -1nx-1 + 3 Simplifying m = -4x-1 + -1nx-1 + 3 Reorder the terms: m = 3 + -1nx-1 + -4x-1
| 2x+9x-7x-5= | | p-8=24 | | e^5x+6=8e^3x | | 4sin^4x-1=0 | | 7(8x+2y)= | | 16=s+7 | | 10w-7-9w=1+7 | | 5x+7y=64 | | 2(6x+1)+4=12x | | 13(923x-76y)=100z | | 2xy+3x^2-60+y=6xy+x^2+150 | | 6(8X-1)-(6X+2)=(8X-3) | | 10x-1=58+(5x-9) | | W^2-10w*24=0 | | 10x-1=58 | | 5x+6y=-20 | | 33b+22a+44c=2581 | | the*crazy*dog=2500000000000 | | 22a+33b+44c=2581 | | 6c-3=-249 | | y(n+1)-3y(n+1)-4y(n)=0 | | 7b+9=-313 | | 1a+2b+3c=10 | | 2p+6=86 | | 2r^2-3r-4=0 | | 5z=90-2z | | 76+x+x+x=180 | | 2(3x-6)=3(2x-5) | | 75+x+x+x=180 | | a+270=-5a-6 | | 100x^3=10000000000 | | 9x-y+4z=-12 |